2019
DOI: 10.1007/s00068-019-01114-4
|View full text |Cite|
|
Sign up to set email alerts
|

Intramedullary screw fixation for simple displaced olecranon fractures

Abstract: Purpose Olecranon fractures are common and typically require surgical fixation due to displacement generated by the pull of the triceps muscle. The most common techniques for repairing olecranon fractures are tension-band wiring or plate fixation, but these methods are associated with high rates of implant-related soft-tissue irritation. Another treatment option is fixation with an intramedullary screw, but less is known about surgical results using this strategy. Thus, the purpose of this study was to report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…Moreover, Bosman in 2020 [3] used 7′3 mm intramedullary screw fixation for simple, displaced fractures in 15 patients with excellent results. They used screws of enough length to engage the narrow marrow of the proximal ulnar diaphysis (typically 90-110) to get a stable fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bosman in 2020 [3] used 7′3 mm intramedullary screw fixation for simple, displaced fractures in 15 patients with excellent results. They used screws of enough length to engage the narrow marrow of the proximal ulnar diaphysis (typically 90-110) to get a stable fixation.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to an incidence of 1.15/10,000 person-years [1][2][3]. The short and medium term outcome of these fractures is generally reported as good [4][5][6][7][8][9][10][11][12][13][14], and the few existing long-term studies, one of which followed olecranon fractures for more than 10 years [15] and another for more than 15 years [2], support a durable outcome with time. No study has to our knowledge evaluated if the favorable long-term outcome accounts for all subtypes of olecranon fractures.…”
Section: Introductionmentioning
confidence: 93%
“…No study has to our knowledge evaluated if the favorable long-term outcome accounts for all subtypes of olecranon fractures. Most shortterm studies have only evaluated if the outcome differs after different type of surgeries [4][5][6][7][8][9][10][11][12][13][14]. On such study inferred that type of surgery are of more importance for the outcome than type of fracture [16], another study supporting this view when reporting no differences when comparing 78 consecutive patients with Mayo type IIA and IIB fractures [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the open reduction and extensive exposure increases the risk for ischemic insult of the growth plate [9]. In 1942, MacAusland described the treatment of olecranon fractures by intramedullary screw xation, but subsequent reports noted that the technique was challenging and unreliable [10][11]. Persiani et al reported the outcomes of treatment of olecranon fractures in children affected with osteogenesis imperfecta (OI) type I by screw xation.…”
Section: Introductionmentioning
confidence: 99%